Design of simulator system for marine-surveillance radar - Nguyen , Trường Giang; Hoang , Trang (Journal of Technical Education Science, 2016)
In this paper, the authors present the design, manufacture of a simulator system for marine-surveillance radar. The objective of this work is to create a practicing system which consists of control program and display like the real ones. Therefore, it helps users to become familiar with the real system. Keyboard, program and hardware for controlling based on PIC-microcontroller are designed and manufactured to match perfectly in size interface language with the actual system which is equipped to soldiers. The display interface is created using C# programming language and works with different scenarios for training purposes